Important criteria for managing disaster Waste in Malaysia - Zawawi, E.M.A.; Yusof, N.S.; Kamaruzzaman, S.N.; Ismail, Z. (Penerbit UTM Press, 2015)
In Malaysia, disaster impacts have become an impediment to the sustainable development. Limited number of case studies has been carried out on the topic of the Disaster Management Guidelines in Malaysia and the needs of the waste management to be adopted into disaster management guidelines. Thus, the main purpose of this study is to highlights possible entry points for waste management adaption into Disaster Management Guidelines in Malaysia. This study will adopt qualitative research design involving comprising of journal review, previous case study and semi-structured interviews. This paper presented the important criteria relating to the disasters waste management in Malaysia. It is anticipated that this research will generate interests from disaster waste researchers and disaster waste management policy makers, as it will provide fundamental elements towards more rigor disaster waste management policy.